The Development of Psychomotor Assessment Instrument Long Jump on Penjaskes Subjects of Class VIII - Maulana, Prahas; Rusilowati, Ani; Soegiyanto, Soegiyanto (Universitas Negeri Semarang, 2018)
Development of the instrument is very important to know the success of learners instructional practices in the long jump. The research aims to produce teacher assessment instruments on valid long jumps psychomotor, reliability and practical. The design of this research using R & D with by referring to the research procedure Sugiyono. The subject of a number of research participants from 30 students to conduct a small-scale test and 90 students for large-scale trials. Data collection using interview techniques, and studies now document. The data were analyzed qualitatively and quantitatively. The results showed that instrument stated in valid content of 0.68. Reliability of the ICC between appraisers of 0.730. Small-scale trials demonstrated the value of 0.652 KMO. And Bartlett's Test sig 0.000. However, there are items of value the MSA < 0.5. large-scale Test showed the value of KMO 0.756 and sig Tests. Bartlett's 0.000. all grains acquire MSA > 0.5. Form 4 instrument components. Reliability of the instrument on a small scale test of 0.802 and large-scale 0.805. Test score of 123 practicalities that means practical instruments used. The findings of this research are the instrument developed proven valid, reliability and practical. The benefits of this research to teachers can use this instrument in the study of sports material long jumps in order to generate an easy and precise measurements.